2004
DOI: 10.1038/sj.eye.6701374
|View full text |Cite
|
Sign up to set email alerts
|

Reducing intraocular pressure: is surgery better than drugs?

Abstract: Reducing IOP is presently the evidence based, most accepted and most practised therapeutical approach for glaucoma patients. Currently topical ocular hypotensive medications, with its different classes, as well as filtering surgery (trabeculectomy and non-penetrating glaucoma surgery) are in the forefront of therapeutic modalities for IOP reduction. This article looks at the potential advantages and disadvantages of topical medications versus filtering surgery. It does not directly address the question of init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 94 publications
(97 reference statements)
0
3
0
Order By: Relevance
“…Shaarawy et al 51 have concluded that these observations constitute a definite advantage of surgery over medical treatment. This is supported by the work of Asrani et al 52 who measured diurnal IOP fluctuation using home tonometry and concluded that diurnal fluctuations contributed to visual field progression.…”
Section: Evidence For Better Outcomes For Surgical or Medical Treatmentsmentioning
confidence: 98%
“…Shaarawy et al 51 have concluded that these observations constitute a definite advantage of surgery over medical treatment. This is supported by the work of Asrani et al 52 who measured diurnal IOP fluctuation using home tonometry and concluded that diurnal fluctuations contributed to visual field progression.…”
Section: Evidence For Better Outcomes For Surgical or Medical Treatmentsmentioning
confidence: 98%
“…Successful glaucoma surgery may be associated with complete or partial suspension of IOP-lowering medications, hence ameliorating ocular surface homeostasis and reducing medicaments-related DED [ 17 ]. Nonetheless, surgery may induce changes for two main reasons: the use of mitomycin C can cause epithelial damage and goblet cell loss [ 18 ]; filtrating bleb also modifies the anatomy of the ocular surface and may induce DED by itself [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“… 6 Reducing IOP is presently the evidence-based, most accepted, and most practiced therapeutic approach of glaucoma patients. 7 Results of key landmark trials have shown that lowering intraocular pressure is the main stay of management. 8 …”
Section: Introductionmentioning
confidence: 99%